FANCD2 promotes mitotic rescue from transcription-mediated replication stress in SETX-deficient cancer cells - Maha Said; Viviana Barra; Elisa Balzano; Ibtissam Talhaoui; Franca Pelliccia; Simona Giunta; Valeria Naim (Communications Biology, 2022)
A synthetic lethal interaction is reported between the R-loop helicase Senataxin (SETX) and Fanconi anemia pathway proteins, with SETX deficiency increasing replication stress-induced chromosome fragility & activation of mitotic DNA synthesis.